2016
DOI: 10.1172/jci77812
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of insulin resistance: integrating signaling pathways and substrate flux

Abstract: In most natural habitats, calorie availability is scarce and unpredictable, necessitating the evolution of systems for the efficient storage and utilization of energy. But in our modern, mechanized society, caloric demands are minimized, while highly palatable, calorie-dense foods and beverages are readily available. These changes have fostered the current pandemic of obesity and comorbid conditions of nonalcoholic fatty liver disease (NAFLD), atherosclerosis, and type 2 diabetes (T2D). Insulin resistance is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
819
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,022 publications
(906 citation statements)
references
References 136 publications
21
819
0
11
Order By: Relevance
“…It seems that lipolysis induced by kin-2 RNAi may not be accompanied by an increase in whole-body energy expenditure so that mobilized lipid metabolites may be redistributed to other tissues, unlike fasting. In mammals, ectopic lipid accumulation in liver or muscle is closely associated with insulin resistance and metabolic diseases (53). Thus, it is feasible that lipolysis induced by kin-2 RNAi may mediate ectopic lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that lipolysis induced by kin-2 RNAi may not be accompanied by an increase in whole-body energy expenditure so that mobilized lipid metabolites may be redistributed to other tissues, unlike fasting. In mammals, ectopic lipid accumulation in liver or muscle is closely associated with insulin resistance and metabolic diseases (53). Thus, it is feasible that lipolysis induced by kin-2 RNAi may mediate ectopic lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, lipodystrophy and cachexia are frequently associated with insulin resistance (83)(84)(85). In addition, there is a close correlation between insulin resistance and hyperlipidemia in metabolic diseases (53). Intriguingly, it has been reported that a human patient lacking FSP27 showed partial lipodystrophy and insulin resistance (86).…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is an example of ectopic fat accumulation in liver and this lipid accumulation is usually associated with insulin resistance, abnormal substrate fluxes [28], increased secretion of hepatokines [29], increased gluconeogenesis, decreased glycogen synthesis and inhibition of insulin signalling pathways [30,31]. When excess hepatic lipid accumulates (NAFLD), it not only has the potential for causing insulin resistance but there is also the potential for chronic liver inflammation, increasing risk of progressive fibrotic liver disease, cirrhosis and hepatocellular carcinoma.…”
Section: Putative Biological Mechanisms By Which Nafld Contributes Tomentioning
confidence: 99%
“…Such an effect occurs in sedentary obese individuals, who do not benefit from the ameliorating effect of increased muscle activity and increased mitochondrial fatty acid oxidation, which would normally buffer the liver from the burden of high FFA levels [33]. With the increased fluxes of long chain fatty acyl CoAs through the liver, evidence is accumulating that hepatic lipid accumulation is capable of promoting hepatic insulin resistance and hepatic inflammation through accumulation of di-acyl glycerols (DAGs) and protein kinase Cε (PKC-ε) activity, inhibiting the insulin signalling pathway and promoting insulin resistance (reviewed in detail in [28]). The conversion from TAG to DAG is mediated by adipose triglyceride lipase (ATGL) and comparative Gene Identification-58 (CGI-58) is an activator of ATGL.…”
Section: Hepatic Lipid Accumulation Insulin Resistance Insulin Cleamentioning
confidence: 99%
See 1 more Smart Citation